Pengetahuan, Sikap dan Keterampilan Masyarakat dalam Pencegahan COVID-19 di DKI Jakarta - Utami, Ressa Andriyani; Mose, Ria Efkelin; Martini, Martini (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2020)
Corona 2019 virus disease (COVID-19) has been designated as a global pandemic by WHO. This disease is caused by SARS-CoV-2. The management program that has been carried out by the Government of Indonesia is the Large-Scale Social Limitation (PSBB) and now it is the Adaptation of New Habits (AKB) or new normal. This effort was made to reduce the spread of COVID-19. This research was conducted to identify the knowledge, attitudes and behavior of the people of DKI Jakarta province towards the prevention of SARS-CoV-2 transmission. This research uses descriptive analysis, distributing closed questions in a randomized online questionnaire to 5 cities in DKI Jakarta Province through social media networks. The number of respondents in this study was 1021. Data were analyzed using descriptive analysis by calculating frequency, percentage, and cross tabulation. Research shows 83% have good knowledge, 70.7% good attitude and 70.3% good skills in COVID prevention 19. It is necessary to conduct strict and massive health promotion and field monitoring in the community so that this pandemic ends soon.